An application of Multifaceted Rasch measurement in the Yes/No Angoff standard setting procedure. (October 2013) - Hsieh, Mingchuan
When implementing standard setting procedures, there are two major concerns: variance between panelists and efficiency in conducting multiple rounds of judgments. With regard to the former, there is concern over the consistency of the cutoff scores made by different panelists. If the cut scores show an inordinately wide range then further rounds of group discussion are required to reach consensus, which in turn leads to the latter concern. The Yes/No Angoff procedure is typically implemented across several rounds. Panelists revise their original decisions for each item based on discussion with co-panelists between each round. The purpose of this paper is to demonstrate a framework for evaluating the judgments in the standard setting process. The Multifaceted Rasch model was applied as a tool to evaluate the quality of standard setting in a context of language assessment. The results indicate that the Multifaceted Rasch model offers a promising approach to examination of the variability in the standard setting procedures. In addition, this model can identify aberrant decision making for each panelist, which can be used as feedback for both standard setting designers and panelists.